2002
DOI: 10.1016/s0076-6879(02)46046-6
|View full text |Cite
|
Sign up to set email alerts
|

[1] Gene therapy for hypertension: The preclinical data

Abstract: Abstract-Despite several drugs for the treatment of hypertension, there are many patients with poorly controlled high blood pressure. This is partly because all of the available drugs are short-lasting (Յ24 hours), have side effects, and are not highly specific. Gene therapy offers a possibility of producing longer-lasting effects with precise specificity based on the genetic design. Preclinical studies on gene therapy for hypertension have taken 2 approaches. Chao et al have performed extensive studies on gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…40,41 Nevertheless, a virus control (AAV.Control-shRNA) and a virus-free control (PBS) were used to exclude possibilities that may complicate interpretation of the experimental data due to the employment of viral vector. Control-shRNA is scrambled in sequence and has been proven, by BD Clontech (Palo Alto, CA, USA), not to interact with any known gene sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Nevertheless, a virus control (AAV.Control-shRNA) and a virus-free control (PBS) were used to exclude possibilities that may complicate interpretation of the experimental data due to the employment of viral vector. Control-shRNA is scrambled in sequence and has been proven, by BD Clontech (Palo Alto, CA, USA), not to interact with any known gene sequence.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the AAV vector can deliver target genes to the nuclei of cells, where the target gene then integrates into the host genome. 40,42 These features make it possible to develop permanent gene therapy for humans using AAV vector. In the present study, we employed AAV-2, which has a high selective affinity, to renal tubule epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Clinical trials conducted in the last two decades have demonstrated that a reduction in blood pressure of 10/ 5 mmHg will result in the decrease in stroke mortality by 40% and coronary heart disease by 20%, regardless of the classes of antihypertensive drugs prescribed. [1][2][3] However, the ratio of goal blood pressure control is very low, especially in the developing countries (about 4%), because current drugs, although effective, have poor compliance, are expensive and short-lasting (hours or one day). Gene therapy may have the potential to solve these problems and provide an effective and stable control of blood pressure for hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…7,[19][20][21] Gene therapy for hypertension is a viable strategy. [1][2][3] The application of kallikrein gene therapy to reduce blood pressure has been tested in several hypertensive rat models, and the results showed that the injection of various kallikrein gene constructs with adenovirus or plasmids caused a significant reduction in systemic blood pressure in SHRs, one-clip Goldblatt hypertensive rats and Dahl-salt-sensitive hypertensive rats. [22][23][24][25][26][27] All those studies, however, were performed using transient expression vectors and provided short-term control of blood pressure (a few weeks), a duration not meeting the requirement for clinical therapy of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy may provide long-term control of blood pressure for hypertensive patients [2] . Recombinant adeno-associated virus (rAAV) is an appealing vector for gene therapy protocols [3] , possibly mediating stable transduction and long-term expression of target genes in vivo.…”
Section: Introductionmentioning
confidence: 99%